Cofiniteness and coassociated primes of local cohomology modules - Aghapournahr, Moharram; Melkersson, Leif (MATHEMATICA SCANDINAVICA, 2009)
Let R be a noetherian ring, a an ideal of R such that R/a=1 and M a finite R-module. We will study cofiniteness and some other properties of the local cohomology modules H^i_a (M). For an arbitrary ideal a and an R-module M (not necessarily finite), we will characterize a-cofinite artinian local cohomology modules. Certain sets of coassociated primes of top local cohomology modules over local rings are characterized.